A FAST BIT-LOADING ALGORITHM FOR HIGH SPEED POWER LINE COMMUNICATIONS - Zhang, Shengqing; Zhao, Li; Zou, Cairong (Journal of electronics (China), 2012)
Adaptive bit-loading is a key technology in high speed power line communications with the Orthogonal Frequency Division Multiplexing （OFDM） modulation technology. According to the real situation of the transmitting power spectrum limited in high speed power line communications, this paper explored the adaptive bit loading algorithm to maximize transmission bit number when transmitting power spectral density and bit error rate are not exceed upper limit. With the charac- teristics of the power line channel, first of all, it obtains the optimal bit loading algorithm, and then provides the improved algorithm to reduce the computational complexity. Based on the analysis and simulation, it offers a non-iterative bit allocation algorithm, and finally the simulation shows that this new algorithm can greatly reduce the computational complexity, and the actual bit allocation results close to optimal.